Association between haemoglobin, albumin, lymphocytes, and platelets and mortality in patients with heart failure - Ling Liu; Benbingdi Gong; Wei Wang; Kai Xu; Kaoshan Wang; Guixian Song (ESC Heart Failure, 2024)
Abstract Aims The combination of haemoglobin, albumin, lymphocytes, and platelets (HALP) is a new metric used to assess patient prognosis in many diseases. This study aimed to assess the relationship between HALP and short‐ and long‐term mortality in patients with heart failure. Methods and results This retrospective cohort study included adult patients with heart failure who were hospitalized between 2019 and 2021. The primary outcomes were 1‐month mortality and 1‐year mortality. The multivariable logistic regression analysis was used to evaluate the association between HALP and the risk of mortality. Stratified analyses were conducted based on New York Heart Association functional classification (NYHA) stage (II/III, IV) and left ventricular ejection fraction (LVEF, <50%, ≥50%). The area under the receiver operating characteristic curve (AUC) was used to evaluate the ability of HALP, prognostic nutritional index (PNI), C‐reactive protein (CRP), and the Meta‐Analysis Global Group in Chronic Heart Failure (MAGGIC‐HF) risk score in predicting mortality in patients with heart failure. A total of 730 patients with heart failure were included, of whom 61 (8.36%) died within 1 month and 77 (10.55%) died within 1 year. High HALP scores were associated with a reduced risk of 1‐month mortality (odds ratio (OR) = 0.978, 95% confidence interval (CI): 0.963–0.992, P = 0.003) and 1‐year mortality (OR = 0.987, 95% CI: 0.977–0.997, P = 0.009) in patients with heart failure. In patients with different NYHA stages or LVEF levels, high HALP scores were correlated with a reduced risk of 1‐year mortality in patients with NYHA stage II/III (OR = 0.978, 95% CI: 0.957–1.000, P = 0.045) or LVEF ≥50% (OR = 0.970, 95% CI: 0.945–0.996, P = 0.024). The AUC for HALP, PNI, CRP, and MAGGIC‐HF to predict 1‐year mortality in patients with heart failure were 0.677 (95% CI: 0.619–0.735), 0.666 (95% CI: 0.608–0.723), 0.638 (95% CI: 0.572–0.704), and 0.654 (95% CI: 0.591–0.717), respectively. Conclusions HALP may be a potential marker for predicting mortality in patients with heart failure. Further exploration based on HALP may yield better clinical predictors of prognosis in patients with heart failure.